2015
DOI: 10.1016/j.apenergy.2015.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of annealing cycles for electric output in outdoor conditions for amorphous silicon photovoltaic–thermal systems

Abstract: Previous studies with fixed operating temperatures have shown that hydrogenated amorphous silicon (a-Si:H) was a promising absorber layer for solar photovoltaic -thermal (PVT) systems because of a) a low temperature coefficient and b) the opportunity to reverse light induced degradation with thermal annealing. This study further refined the simulation of the optimal dispatch strategy for a-Si:H based PVT by studying annealing cycles and analysis of the degradation at other operating temperatures controlled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The variation of the normalized electrical performance is displayed in Fig. 10, and the result is consistent with that found by Rozario et al [13]. The electrical efficiencies of a-Si cells degrade by 11.5% and 6.5% at 30 °C and 60 °C, respectively.…”
Section: Power Generationsupporting
confidence: 88%
See 1 more Smart Citation
“…The variation of the normalized electrical performance is displayed in Fig. 10, and the result is consistent with that found by Rozario et al [13]. The electrical efficiencies of a-Si cells degrade by 11.5% and 6.5% at 30 °C and 60 °C, respectively.…”
Section: Power Generationsupporting
confidence: 88%
“…The controlled light-soaking tests on a-Si cells at different temperatures indicated that cycling and changing the exposure temperature modified the efficiency of a-Si cells between 10% and 17% in a recurrent pattern [11]. The a-Si cells could reach higher stabilized efficiencies at higher operating temperatures and the stabilized performance levels depended largely on light exposure and a characteristic temperature [12,13]. Moreover, higher temperatures resulted in faster degradation in the early stages of the degenerated process [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of temperature on a-Si PV/T systems is rarely reported so far. Although Rozario et al [14] and Pathak et al [15] proposed the PV/T system using a-Si cells, the study on the electrical performance is based solely on a-Si cells rather than PV/T system. Especially the PV/T systems always operate in recurrent alternating heating and cooling conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…A PVT collector coupled to a new heat input process of use for the desalination process has been proposed by Fine et al [25]. A complete study of a PVT collector using hydrogenated amorphous silicon (a‐Si: H) as an absorbent layer was modelled [26] and its performance was analysed using available data. Many systems capable of satisfying both the heating and the cooling of the building are studied by Entchev et al [27].…”
Section: Introductionmentioning
confidence: 99%